Karsinoma Sel Squamosa - - Sagiran (Universitas Muhammadiyah Yogyakarta, 2003)
Squamous cell carcinoma is a non-melanotic skin cancer that commonly found beside basal cell carcinoma. The lesion is specific with the thickening of stratum corneum of the skin. The common predilection is in the face, it can follow the subsequent process of skin trauma. We reported the case of a 60- year old female with a squamous cell carcinoma in her lower lip. She has been suffering from this disease for 5 years, but there is no metastasis. It has been wide-excised, histo-pathologically showed that the margin of excision is tu¬mor-free.Karsinoma sel squamosa adalah salah satu bentuk keganasan kulit non-melanotik yang sering dijumpai, di samping karsinoma sel basal. Lesinya sangat khas dengan adanya penebalan lapisan tanduk. Predileksi yang sering adalah wajah, dapat mengikuti proses penyembuhan pasca trauma. Tulisan ini melaporkan sebuah kasus seorang perempuan 60 tahun dengan karsinoma sel squamosa pada bibir bawah. Penyakitnya sudah diderita 5 tahun, namun tidak didapatkan metastasis. Telah dilakukan eksisi luas, histopatologis menunjukkan tepi irisan bebas dari tumor.